2021
DOI: 10.3390/e23111507
|View full text |Cite
|
Sign up to set email alerts
|

Bird Species Identification Using Spectrogram Based on Multi-Channel Fusion of DCNNs

Abstract: Deep convolutional neural networks (DCNNs) have achieved breakthrough performance on bird species identification using a spectrogram of bird vocalization. Aiming at the imbalance of the bird vocalization dataset, a single feature identification model (SFIM) with residual blocks and modified, weighted, cross-entropy function was proposed. To further improve the identification accuracy, two multi-channel fusion methods were built with three SFIMs. One of these fused the outputs of the feature extraction parts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…On the other hand, Zhang et al proposed a method that can achieve outstanding bird sound classification accuracy based on deep CNNs (DCNNs) [4,13]. Specifically, they calculated spectrograms of the short-time Fourier transform, Mel-frequency transform, and Chirplet transform for animal sounds, constructed individual DCNN models for each spectrogram, and predicted bird species by combining the features from the DCNN models.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Zhang et al proposed a method that can achieve outstanding bird sound classification accuracy based on deep CNNs (DCNNs) [4,13]. Specifically, they calculated spectrograms of the short-time Fourier transform, Mel-frequency transform, and Chirplet transform for animal sounds, constructed individual DCNN models for each spectrogram, and predicted bird species by combining the features from the DCNN models.…”
Section: Related Workmentioning
confidence: 99%
“…ASC is particularly useful when visual identification is challenging, such as regarding small, nocturnal, and camouflaged animals [2]. Recently, deep learning-based models, such as convolutional neural networks (CNNs), have demonstrated superior performance in ASC as well as in other signal processing applications [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…ASC is a particularly useful tool for cases where visual identification is difficult, such as small animals, nocturnal animals, and camouflaged animals. Recently, deep learning-based models such as convolutional neural networks (CNNs) have been widely used in ASC [ 2 , 3 ] as well as other signal processing applications. Although they show excellent classification performance by using temporal and frequency characteristics suitable for sound classification, their performance is greatly affected by the quality and quantity of the animal sound data used for learning.…”
Section: Introductionmentioning
confidence: 99%
“…Cross−modalities method is another research direction in identifying bird calls. Zhang et al [ 46 ] combined the STFT−spectrogram, Mel−spectrogram, and Chirplet−spectrogram as input features and used CNN to identify 18 bird species. The results demonstrated that the best mAP reached 91.4%.…”
Section: Introductionmentioning
confidence: 99%